2006
DOI: 10.1111/j.1440-0960.2006.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis to sodium benzoate chloroacetamide in a sorbolene lotion

Abstract: Sodium benzoate chloroacetamide is sometimes used as a combination preservative in cosmetics to prevent the growth of bacteria, mould, fungi and yeasts. A case of occupational allergic contact dermatitis to this preservative is described in a 32-year-old female personal care assistant, who was found to have allergic contact dermatitis involving the hands, caused by the sorbolene lotion supplied in her workplace. Patch testing to chloroacetamide, sodium benzoate chloroacetamide and the sorbolene lotion was posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Chloroacetamide is thought to be the allergen. Some of the reported cases have confirmed this by having their patients patch tested and demonstrating a negative reaction to sodium benzoate …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Chloroacetamide is thought to be the allergen. Some of the reported cases have confirmed this by having their patients patch tested and demonstrating a negative reaction to sodium benzoate …”
Section: Discussionmentioning
confidence: 74%
“…The recent Scientific Committee on Consumer Safety (SCCS) of the EU compiled all reported cases of chloroacetamide allergy, including data from Australia, and reported an allergy frequency rate of approximately 1% . Reported cases in the literature were linked to sorbolene lotion, roll‐on deodorant, wall paint, leather shoes and anti‐wrinkle serum . Chloroacetamide is also used as a biocide in soluble cutting oils and in the leather, paper, textile and plastic industries…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, products containing SB-such as make-up cleaning wipes, cosmetics, sanitary pads, toys, lotions, and toothpaste-may cause allergic contact dermatitis and/or contact urticaria. [5][6][7] Reports of urticaria, angioedema, rhinitis, asthma, and even anaphylactic shock following oral intake or inhalation of SB are considered rare. 8 Michils et al 4 reported the case of a 19-year-old adult who developed anaphylaxis from SB-containing cheese.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the nine papers found in the literature, three papers (Brasch and Uter, 2011 ; Schnuch et al., 2011 ; Schalock et al., 2017 ) reported a possible skin sensitising effect and five papers, which mentioned or investigated the skin sensitisation effect of sodium benzoate, concluded on the absence of skin sensitisation of sodium benzoate. One paper reported a case of allergic contact dermatitis to sodium benzoate chloracetamide (Sutton and Nixon, 2006 ); however, the patient tested negative to sodium benzoate alone. Based on the above, the FEEDAP Panel reiterates that the additive should be considered as a potential skin sensitiser.…”
Section: Assessmentmentioning
confidence: 99%